RELASI ANTARTOKOH DAN LINGKUNGAN ALAM DALAM NOVEL SERDADU PANTAI KARYA LAODE INSAN: KAJIAN EKOKRITIK GLOTFELTY - Nur, Dian Annisya; Juanda, Juanda; Saguni, Suarni Syam; Afandi, Iswan (Universitas Negeri Makassar, 2024)
This study analyzes the relationship between characters and nature in the novel Serdadu Pantai using Glotfelty's ecocriticism theory. The research method applied is qualitative descriptive, focusing on the depiction of nature, the relationship between characters and the environment, and the ecological values conveyed by the author. The findings reveal three main points: 1) the depiction of nature is divided into physical descriptions and atmospheres that influence the story; 2) the emotional relationships between characters and nature illustrate character development through interactions with the environment; and 3) ecological messages are delivered through story and symbolism, emphasizing the importance of environmental conservation. This study provides new insights into the significance of environmental care and enriches ecocriticism studies in Indonesian literature.